2013
DOI: 10.1111/psj.12010
|View full text |Cite
|
Sign up to set email alerts
|

Policy Perspectives on National Security and Foreign Policy Decision Making

Abstract: This article reviews major decision‐making models with an emphasis on basic theoretical perspectives as well as on how these models explain foreign policy decision making and national and international security decisions. Furthermore, we examine how these models have been utilized in explanations of various international crises. Specifically, for each model, we present examples drawn from the literature on applications of the respective model to foreign policy and national security decisions. The theories we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 115 publications
(201 reference statements)
0
11
0
Order By: Relevance
“…While their work indicates that rational choice theory is the point of comparison for most studies in the field, it is also the point of departure that takes the field in very different directions. As a result, the authors speculate, “Perhaps these considerations help to explain the diversity of decision‐making theories and the lack of a central theme in how they are applied to real‐world events” (Redd & Mintz, , p. S30). They conclude by suggesting that future work on national security and foreign policy decision making should apply multiple theories to single events in order to maximize explanatory power.…”
Section: Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…While their work indicates that rational choice theory is the point of comparison for most studies in the field, it is also the point of departure that takes the field in very different directions. As a result, the authors speculate, “Perhaps these considerations help to explain the diversity of decision‐making theories and the lack of a central theme in how they are applied to real‐world events” (Redd & Mintz, , p. S30). They conclude by suggesting that future work on national security and foreign policy decision making should apply multiple theories to single events in order to maximize explanatory power.…”
Section: Processesmentioning
confidence: 99%
“…Clearly, policy scholars have played an important role in evaluating and explaining some of the most important national security and foreign policy decisions and events in modern history. Redd and Mintz () present a comprehensive review of the works on decision making in the policy studies literature as related to national security and foreign policy. The authors discuss several theories and models, including rational choice, cybernetic model, prospect theory, poliheuristic theory, organizational and bureaucratic politics, groupthink and polythink, analogical reasoning, applied decision analysis, and biased decision making.…”
Section: Processesmentioning
confidence: 99%
“…15 The application of different decision-making models to the security field has shown the existence of many reasons why decision-making in complex situations can fail. To take a few examples, 16 the cybernetic theory has shown that decisionmakers have limited capabilities for rational decision-making. The prospect theory demonstrates that decision-makers will think not only about solving the problems, but also about their personal and political gains and losses.…”
Section: Comprehensive Approaches To Securitymentioning
confidence: 99%
“…Each year we solicit recommendations for advanced graduate students, working under the guidance of (and often as co‐authors with) leading public policy scholars to write the review articles. Previous essays covered topics including: agenda‐setting (Pump, ), policy analysis (Carlson, ), policy history (deLeon & Gallagher, ), policy process theories (Nowlin, ), public opinion (Mullinix, ), defense and security (Ripberger, ), education policy (Conner & Rabovsky, ), governance (Robichau, ), comparative public policy (Gupta, ), economic policy (Pump, ), environmental policy (Niles & Lubell, ), health policy (Haeder, ), social policy (Guzman, Pirog, & Seefeldt, ), law and public policy (Kreis & Christensen, ), and international relations and policy (Redd & Mintz, ). This year's special issue includes the first of our review articles to be in the second iteration for their theoretical issue areas in the Yearbook .…”
Section: Policy Scholarship: New Developments Snapshots and Trendsmentioning
confidence: 99%